2019
DOI: 10.1038/s41375-019-0580-z
|View full text |Cite
|
Sign up to set email alerts
|

Retention of CD19 intron 2 contributes to CART-19 resistance in leukemias with subclonal frameshift mutations in CD19

Abstract: Every successful cancer therapy story has Exhibit B, comprised of patients who either did not respond to the initial treatment or acquired resistance after a seemingly curative intervention. The CD19-directed chimeric antigen receptorarmed T-cell therapy (commonly known as CART-19) is the case in point. Although it has revolutionized treatment for B-cell acute lymphoblastic leukemia (B-ALL) in children and adults and gained swift FDA approval,~30% of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 22 publications
(22 reference statements)
6
54
0
Order By: Relevance
“…1e ). We observed that both samples express a previously described 18 nonfunctional CD19 transcript retaining intron 2 (Supplementary Fig. 4c ).…”
Section: Resultssupporting
confidence: 60%
“…1e ). We observed that both samples express a previously described 18 nonfunctional CD19 transcript retaining intron 2 (Supplementary Fig. 4c ).…”
Section: Resultssupporting
confidence: 60%
“…Moreover, the dysregulation of some of these splicing factors could control the expression of at least a subset of circRNAs that would then entail important functional consequences that could contribute to neoplastic transformation of B-cells. This has already been shown by us in the context of aberrant splicing of SRSF3-dependent mRNA transcript encoding CD19 (Asnani, 2019;Black et al, 2018;Sotillo et al, 2015), but here we provide increasing evidence that gene dysregulation could also occur via circRNAs.…”
Section: Introductionsupporting
confidence: 78%
“…LR-seq of human and mouse cell and tissue transcriptomes has revealed a rich diversity of spliced isoforms (Tilgner et al, 2015;Lagarde et al, 2017;Byrne et al, 2017;Tilgner et al, 2018;Workman et al, 2019;Sheynkman et al, 2020). In cancer research, the use of LR-seq to identify primary tumorassociated spliced isoforms remains underexploited and has been limited to the study of human leukemia samples (Asnani et al, 2020;Tang et al, 2020). Importantly, the ability to aquire the depth of coverage needed to accurately quantitate transcripts using LR data is prohibitively expensive.…”
Section: Introductionmentioning
confidence: 99%